2022
DOI: 10.3390/ijerph20010680
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Anxiety and Wellbeing at Work in Finland during 2020–2022: A 5-Wave Longitudinal Survey Study

Abstract: Background: The COVID-19 pandemic impacted workers globally during 2020–2022 and it has had major psychological implications for workers’ wellbeing. This longitudinal study analyzed risk and protective factors predicting COVID-19 anxiety among workers in Finland. Longitudinal national sample of Finnish workers (n = 685) participated in a five-wave study conducted in 2020–2022, covering multiple waves of the COVID-19 pandemic and its aftermath. Our outcome measure was COVID-19 anxiety. Predictors were psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Oksanen and colleagues [ 25 ] have found that remote work seemed to be a softer change for those who had already used it as part of their work. However, overall, people working remotely experienced more anxiety, and the most challenging time was in the middle of the pandemic in Finland [ 26 ] and employees who felt stress related to online environment, or had feelings of overwhelming or loneliness, experienced anxiety or concerns more. Specifically, being female or younger was connected to feelings of anxiety [ 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oksanen and colleagues [ 25 ] have found that remote work seemed to be a softer change for those who had already used it as part of their work. However, overall, people working remotely experienced more anxiety, and the most challenging time was in the middle of the pandemic in Finland [ 26 ] and employees who felt stress related to online environment, or had feelings of overwhelming or loneliness, experienced anxiety or concerns more. Specifically, being female or younger was connected to feelings of anxiety [ 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, overall, people working remotely experienced more anxiety, and the most challenging time was in the middle of the pandemic in Finland [ 26 ] and employees who felt stress related to online environment, or had feelings of overwhelming or loneliness, experienced anxiety or concerns more. Specifically, being female or younger was connected to feelings of anxiety [ 11 , 26 ]. Perceived stress was found to be related to work ability, but also to a lack of ergonomics and support from the working organisation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study investigated the self-reported physical and mental health symptoms of SARS-CoV-2infected inpatients discharged home. Respondents were presented a list of health conditions whose presence or absence they reported [28][29][30][31]. These included: persistent weight loss, loss of sense of smell, loss of sense of taste, fever, cold, sore throat, sensations of burning or electricity in upper and lower limbs, persistent paresthesia in the hands or feet, a mobility disorder in one of the limbs, shortness of breath at rest and during daily activities, daily coughing, pain or discomfort in the chest area, hair loss, headaches, muscle aches, the need for home-care since leaving hospital, fatigue and other health conditions reported by the responder.…”
Section: Health Symptoms After a Sars-cov-2 Infectionmentioning
confidence: 99%
“…These changes also connoted different working conditions for mental health workers, and congruently, altered personal perceptions and emotional reactions. Although COVID anxiety had significantly decreased, psychological distress, work exhaustion, perceived loneliness, and social support indicators did not change substantially ( 8 ).…”
Section: Introductionmentioning
confidence: 99%